2021
DOI: 10.3390/s21206801
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity and Frequency Power Alterations during P300 Task as a Result of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic Lateral Sclerosis (ALS) is one of the most aggressive neurodegenerative diseases and is now recognized as a multisystem network disorder with impaired connectivity. Further research for the understanding of the nature of its cognitive affections is necessary to monitor and detect the disease, so this work provides insight into the neural alterations occurring in ALS patients during a cognitive task (P300 oddball paradigm) by measuring connectivity and the power and latency of the frequency-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, Iyer et al, ( Iyer et al, 2015 ) showed increased assortativity in the alpha-band in ALS patients as compared to controls, as well as higher clustering coefficient values based on Partial Directed connectivity (PCD). Similarly, an EEG study conducted by Perez Ortiz et al ( Perez-Ortiz et al, 2021 ) displayed the presence of connectivity alterations (in the sense of reduced synchronisation) in the alpha band in ALS patients during the execution of cognitive tasks. According to Fraschini et al ( Fraschini et al, 2018 ) ALS patients showed reduced brain functional connectivity compared to healthy subjects, which was linked to different synchrony patterns in the alpha band.…”
Section: Discussionmentioning
confidence: 77%
“…For example, Iyer et al, ( Iyer et al, 2015 ) showed increased assortativity in the alpha-band in ALS patients as compared to controls, as well as higher clustering coefficient values based on Partial Directed connectivity (PCD). Similarly, an EEG study conducted by Perez Ortiz et al ( Perez-Ortiz et al, 2021 ) displayed the presence of connectivity alterations (in the sense of reduced synchronisation) in the alpha band in ALS patients during the execution of cognitive tasks. According to Fraschini et al ( Fraschini et al, 2018 ) ALS patients showed reduced brain functional connectivity compared to healthy subjects, which was linked to different synchrony patterns in the alpha band.…”
Section: Discussionmentioning
confidence: 77%
“…This enables the measure to reveal temporal changes of connectivity and opens a new direction for further research. This can be especially useful for analyzing human brain networks in auditory and visual tasks [39,40] and is also promising for assessing motor skills [41]. This also allows us to observe changes in the organization of brain network connectivity over time using well-known measures from complex network graph theory [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, support vector machines were used by Chang et al to classify ALS patients and healthy subjects using plasma biomarkers metrics, achieving a mean accuracy of 88% [44]. Additionally, the research presented by Perez-Ortiz et al showed that EEG activity monitoring, coupled with a support vector machine classifier, can also be used for ALS diagnosis [45], leading to a success rate of 89%. Research by Bandini et al was conducted to distinguish between presymptomatic and symptomatic ALS stages using SVM and KNN algorithms [46].…”
Section: Als Diagnosismentioning
confidence: 99%